Mineralocorticoid Receptor Antagonists Therapy in Resistant Hypertension: Time to Implement Guidelines! - Maiolino, Giuseppe; Azzolini, Matteo; Rossi, Gian Paolo (Frontiers in Cardiovascular Medicine, 2015)
Despite the availability of anti-hypertensive medications with increasing efficacy up to 50% of hypertensive patients have blood pressure levels (BP) not at the goals set by international societies. Some of these patients are either not optimally treated or are non adherent to the prescribed drugs, however, a relevant proportion, despite adequate treatment, have resistant hypertension (RH), which represents an important problem in that is associated to an excess risk of cardiovascular events. Notwithstanding a complex pathogenesis, an abundance of data suggests a key contribution for the mineralocorticoid receptor in RH, thus fostering a potential role for its antagonists in this field. Based on these premises randomized clinical trials have been completed aimed at testing the efficacy of mineralocorticoid receptor antagonists (MRA)s in RH patients and demonstrated their efficacy in reducing BP and markers of target organ damage, such as microalbuminuria, compared to either placebo or other drugs. In summary, owing to the role of the mineralocorticoid receptors in the pathogenesis of RH and on their efficacy proved by randomized clinical trials we advocate the inclusion of MRAs as a forth line therapy in patients with RH.